Bright spots in agricultural landscapes: Identifying areas exceeding expectations for multifunctionality and biodiversity. Issue 6 (25th June 2018) - Frei, Barbara; Renard, Delphine; Mitchell, Matthew G. E.; Seufert, Verena; Chaplin‐Kramer, Rebecca; Rhemtulla, Jeanine M.; Bennett, Elena M.
Abstract: Agriculture's influence on humanity is a dichotomy of promise and peril. Research on the food‐environment dilemma has highlighted the environmental consequences of food production, yet the identification of management solutions is an ongoing challenge. We suggest "bright spots" as a promising tool to identify levers of change by finding areas that exceed expectations for goals, such as agricultural landscape multifunctionality and biodiversity. We identified bright, dark and average spots within a complex agricultural landscape and explored the associated socioeconomic patterns. We found that areas exceeding expectations for biodiversity and landscape multifunctionality were neither spatially congruent nor in conflict. It was more common for areas to underperform (dark spots) for both biodiversity and multifunctionality than over perform for both (bright spots). While dark spots for multifunctionality were alike in their ecosystem service composition, bright spots were bright in multiple, diverse ways. The socioeconomic attributes that characterize bright and darks spots included both farm characteristics as well as farming practices, suggesting that both have potential to be levers of change. Synthesis and applications . Our results suggest that while biodiversity and landscape multifunctionality show similar spatial patterns due to underlying biophysical drivers, managing for biodiversity or landscape multifunctionality alone will not implicitly achieve the other in this system. Bright spots (areas exceeding expectations) in multifunctionality were associated with many different combinations of ecosystem services, but dark spots were uniquely agricultural intensive areas devoted to maximizing crop production at the expense of all other services. From a management perspective, specific farm characteristics and farming practices may impact the potential for multifunctionality: increased mechanization, increased agricultural inputs and larger farm size and capital were associated with dark spots, while smaller farms with potentially greater space for innovation were associated with bright spots. Abstract : Our results suggest that while biodiversity and landscape multifunctionality show similar spatial patterns due to underlying biophysical drivers, managing for biodiversity or landscape multifunctionality alone will not implicitly achieve the other in this system. Bright spots (areas exceeding expectations) in multifunctionality were associated with many different combinations of ecosystem services, but dark spots were uniquely agricultural intensive areas devoted to maximizing crop production at the expense of all other services. From a management perspective, specific farm characteristics and farming practices may impact the potential for multifunctionality: increased mechanization, increased agricultural inputs and larger farm size and capital were associated with dark spots, while smaller farms with potentially greater space for innovation were associated with bright spots.